Nitric Oxide-Releasing S-Nitrosoglutathione-Conjugated Poly(Lactic-Co-Glycolic Acid) Nanoparticles for the Treatment of MRSA-Infected Cutaneous Wounds - Lee, Juho (Pharmaceutics, 2020)
S-nitrosoglutathione (GSNO) has emerged as a potent agent for the treatment of infected cutaneous wounds. However, fabrication of GSNO-containing nanoparticles has been challenging due to its high hydrophilicity and degradability. The present study aimed to fabricate nanoparticles using newly synthesized GSNO-conjugated poly(lactic-co-glycolic acid) (PLGA) (GSNO-PLGA; GPNPs). Since hydrophilic GSNO was covalently bound to hydrophobic PLGA, loss of GSNO during the nanoparticle fabrication process was minimized, resulting in sufficient loading efficiency (2.32% of GSNO, 0.07 μmol/mg of NO). Real-time NO release analysis revealed biphasic NO release by GPNPs, including initial burst release within 3 min and continuous controlled release for up to 11.27 h, due to the differential degradation rates of the –SNO groups located at the surface and inside of GPNPs. Since GPNPs could deliver NO more efficiently than GSNO in response to increased interaction with bacteria, the former showed enhanced antibacterial effects against methicillin-resistant Staphylococcus aureus (MRSA) at the same equivalent concentrations of NO. Finally, the facilitating effects of GPNPs on infected wound healing were demonstrated in MRSA-challenged full-thickness wound mouse model. Collectively, the results suggested GPNPs as an ideal nanoparticle formulation for the treatment of MRSA-infected cutaneous wounds.